Isoimperatorin therapeutic effect against aluminum induced neurotoxicity in albino mice - Rajendran, Peramaiyan; Althumairy, Duaa; Bani-Ismail, Mohammad; Bekhet, Gamal M.; Ahmed, Emad A. (Frontiers in Pharmacology, 2023)
Background: Although aluminum (Al) is not biologically crucial to the human body, classical studies have demonstrated that excessive human exposure to Al can induce oxidative damage, neuroinflammatory conditions and neurotoxic manifestations implicated in Alzheimer’s disease. Exposure to Al was reported to be associated with oxidative damage, neuroinflammation, and to enhance progressive multiregional neurodegeneration in animal models. A good candidate still to be tested is an active natural furanocoumarin, the isoimperatorin (IMP) that can be extracted from Lemon and lime oils and other plants. Here, we examined the neuroprotective effects of IMP on aluminum chloride (Alcl3)-induced neurotoxicity in albino mice. Methods: Twenty-four male albino mice were used in this study. Mice were randomly devided into 5 groups. The first group was given distilled water as a control, the second group was given Alcl3 orally (10 mg/wt/day) starting from the second week to the end of the sixth week, the third group received Alcl3 orally and IMP interperitoneally, i.p. (30 mg/wt/day) starting from week 2 till week 6 where IMP was supplement 1st and then 4 h later Alcl3 was given to mice. The fourth group received the control (IMP 30 mg/wt, i.p.) from the 2nd week till the end of the experiment. Rodent models of central nervous system disorders were assessed using object location memory and Y-maze tests in 6th week began. Essential anti-inflammatory and oxidative stress indicators were evaluated. In addition, serum levels of brain neurotransmitters such as corticosterone, acetylcholine, dopamine and serotonin in brain homogenates were measured calorimetrically. Results: The study results revealed that the daily treatment of Alcl3 upregulated the TNF-α and IL-1β levels, increased MDA accumulation, and decreased TAC and CAT activity. In addition, aluminum induced a reduction in concentrations of ACh, serotonin and dopamine in the brain. However, IMP significantly ameliorates the effect of Alcl3 through modulating the antioxidant and regulating the inflammatory response through targeting Nrf2 and mitogen-activated protein kinase. Conclusion: Thus, IMP might be a promising treatment option for neurotoxicity and neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, which are associated with neuro-inflammation and oxidative stress.